การศึกษาวิเคราะห์และพัฒนารูปแบบการบริหารจัดการเครือข่ายสถานศึกษา ในเขตพื้นที่ชนบทภาคตะวันออกเฉียงเหนือ - วิชัย แสงศรี (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
To analyze the difficulties of school network administration model in northeastern rural area. The research methods comprised five steps. Step 1: Study the conditions of difficulties in school network administration pattern in northeastern rural area, Step 2: Study the conditions and model in school network administration and best practices, Step 3: Generate the school network administration model, Step 4: Evaluate propriety and possibility in the school network administration model, Step 5: Improve and present the school network administration model. Data collections comprised document analysis, questionnaire, interview and observation. The data analysis for this study was employing content analysis and descriptive statistics: frequencies, percentage, mean and standard deviation. The research findings are summarized as follow: 1. It was found that the school network administration in northeastern rural areas concerning the personnel administration’s problems at the highest level in overall and the next in ranging order were budget administration, general affair administration and academic administration. Those problems came from the ambiguous structure of the school network, lacking of law support and insufficiency of all participant in the community. 2. The perceives condition of the school network administration in northeastern rural areas would be the administrative technique which enhance the chance of cooperation among all participant in the community. This means the participants are allowed to take part in planning the learners developing plan and having their role in mobilizing resources. Defining concrete framework, especially concise role and scope of task, also consider significant for developing the success network. Also, the good leadership and well association or good inter-relationship in order to reach localization are needed for driving and monitoring the success of developing learners’ quality. 3. The appropriately and potentiality school network administration model in northeastern rural areas is SEAL Model which consisted of four sections: Section 1 : Name and background of the model : 1) Name of model 2) Rational and significant 3) Principle and theory 4) Objective. Section 2 : The components of the model : 1) School network administration center, 2) Frame work and mission of the school network, 3) Educational community which is the main driven mechanism. 4) Association, Team developing and Leader quality. Section 3 : Application: Implementation for administrators and participants. Section 4 : Condition or key success factor of the model usage.